Stem Education and The Learning of Mathematics in Vulnerable Populations - Cuéllar Guarnizo, Jairo Alberto; Hernández Álvarez, Wilmer; Gutiérrez Cárdenas, Marco Antonio; Vega-Santofimio, Hayley Dahiana (Ingeniería Solidaria, 2022)
Introduction: This article is the product of a project developed by UNIMINUTO in the nineth grade of the Educational Institution Simón Bolivar in “La Nohora” neighbourhood of the Villavicencio - Colombia, this project was executed during 2017 and 2018.Problem: The problem is the low academic performance of students in mathematics, in addition to multiple possible adverse situations they face as a vulnerable population.Objective: The objective is to have a positive impact on the academic performance of the students.Methodology: In the strategy development, STEM education was used to support the learning of math through six sessions were carried out your own classroom. The students solved challenges by programming robots.Results: Complete each challenge had an important attitudinal impact on the students, the joy and satisfaction of them were an unexpected result. A previous knowledge test was carried out at beginning and at the end of the sessions a formative test was applied too. Afterwards, the results of both tests were compared to evidence improvements in the students' mathematical skills.Conclusions: It was possible to provide the target population with an alternative to understand issues mistakenly considered difficult and to propose important playful and didactic moments in cognitive development.Originality: This article shows an educational innovation that the team of researchers will continue to apply. through new projects that allow financing the purchase of equipment and the logistics of the workshops.Limitations: Lack of strategic alliances that allow financing more meetings with students and the acquisition of more robots.
Keywords: educational robotics; STEM education; math learning; robots and math